Nicotine: Carcinogenicity and Effects on Response to Cancer Treatment – A Review - Sanner, Tore; Grimsrud, Tom K. (Frontiers in Oncology, 2015)
Tobacco use is considered the single most important man-made cause of cancer that can be avoided. The evidence that nicotine is involved in cancer development is reviewed and discussed in this paper. Both tobacco smoke and tobacco products for oral use contain a number of carcinogenic substances such as polycyclic hydrocarbons (PAH) and tobacco-specific N-nitrosamines (TSNA) which undoubtedly contribute to tobacco related cancer. Recent studies have shown that nicotine can affect several important steps in the development of cancer, and suggest that it may cause aggravation and recurrence of the disease. TSNA may be formed from nicotine in the body. The role of nicotine as the major addictive component of tobacco products may have distracted our attention from toxicological effects on cell growth, angiogenesis and tumor malignancy. Effects on cancer disease are important aspects in the evaluation of possible long-term effects from sources of nicotine, such as e-cigarettes and products for nicotine replacement therapy (NRT), which both have a potential for life-long use.